Arctic Amplification of Precipitation Changes—The Energy Hypothesis - Pithan, Felix; Jung, Thomas; Jung, Thomas; 1 Helmholtz Centre for Polar and Marine Sciences Alfred‐Wegener‐Institute Bremerhaven Germany (Geophysical Research Letters, 2021)
Temperature and precipitation change more strongly in the Arctic than at lower latitudes, with central Arctic boreal winter precipitation projected to double in the 21st century in a high‐emission scenario. This enhanced hydrological sensitivity has been explained in terms of the Arctic moisture budget and attributed to either moisture advection or surface evaporation. Here, we show that boreal winter moisture availability is less sensitive to surface temperature change in the Arctic than at lower latitudes, questioning a central role of the moisture budget. Hydrological sensitivity, that is, precipitation change per unit temperature change, is similar in models with or without sea‐ice changes, suggesting a secondary role of surface flux changes. Instead, we propose that the Arctic's larger hydrological sensitivity is energetically driven. Increases in latent heat release from precipitation locally balance increased atmospheric radiative cooling in Arctic winter, consistent with process‐level understanding of radiatively driven cloud and precipitation formation. Plain Language Summary: As Earth's climate warms, globally averaged precipitation increases. Both warming and precipitation increase are larger in the Arctic than at lower latitudes. In the atmospheric energy budget, changes in precipitation correspond to changes in latent heat release and must be balanced by advection, surface fluxes, or radiation. This article shows that stronger Arctic than lower‐latitude precipitation increases are mostly driven by stronger radiative loss of energy to space. Previous research had suggested that increased evaporation following the retreat of sea ice was a key driver of Arctic precipitation increases. Understanding the causes of amplified Arctic precipitation change is important to build confidence in model projections and to focus on the most important processes in further research and model development. The link between hydrological and radiative changes also allows to reconcile these two perspectives on Arctic ...